Skeleton key - Horowitz, Anthony, 1955- (New York : Speak, 2006)
Reluctant teenage-spy Alex Rider, on a routine mission at the Wimbledon tennis championships, gets caught up in Chinese gangs, illegal nuclear weapons, and the suspect plans of his Russian host, General Sarov.
Originally published: New York : Philomel Books, 2003.
5.1
5-8
5-8
Wilson's Junior High School
School Library Journal
Keywords: Spies -- Juvenile fiction; Tennis -- Juvenile fiction; Terrorism -- Juvenile fiction; Orphans -- Juvenile fiction; England -- Juvenile fiction; Spies -- Fiction; Tennis -- Fiction; Terrorism -- Fiction; Orphans -- Fiction; England -- Fiction; Spies -- Fiction; Tennis -- Fiction; Terrorism -- Fiction; Orphans -- Fiction; England -- Fiction; Adventure fiction; Spy stories; Adventure fiction; Spy stories